2002
DOI: 10.1034/j.1600-0412.2002.810207.x
|View full text |Cite
|
Sign up to set email alerts
|

Embryo transfer after 2 or 5 days of IVF culture: a retrospective comparison

Abstract: Prolongation of embryo culture from day 2 to day 5 did not improve the clinical outcome of the IVF treatment when measured as baby take home rate. Therefore, for the time being, this strategy does not increase our chances to move towards single embryo transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
(49 reference statements)
0
7
1
Order By: Relevance
“…Although high pregnancy (50±70%) and implantation (30±50%) rates have been reported for blastocysts transfers (Gardner et al, 1998;Marek et al, 1999;Langley et al, 2001) the clinical evidence on the preference of blastocyst transfers to cleavage stage embryo transfers is still controversial. Several prospective studies have shown the superiority of blastocyst transfers over day 2/3 embryo transfers (Gardner et al, 1998;Van Der Auwera et al, 2002), while others have been unable to con®rm these ®ndings (Scholtes and Zeilmaker, 1996;Coskun et al, 2000;Huisman et al, 2000;Lundqvist et al, 2002). In a recent study (Rienzi et al, 2002), day 3 embryo transfers with combined evaluation at pronuclear and cleavage stages demonstrated similar results to blastocyst transfers.…”
Section: Discussionmentioning
confidence: 97%
“…Although high pregnancy (50±70%) and implantation (30±50%) rates have been reported for blastocysts transfers (Gardner et al, 1998;Marek et al, 1999;Langley et al, 2001) the clinical evidence on the preference of blastocyst transfers to cleavage stage embryo transfers is still controversial. Several prospective studies have shown the superiority of blastocyst transfers over day 2/3 embryo transfers (Gardner et al, 1998;Van Der Auwera et al, 2002), while others have been unable to con®rm these ®ndings (Scholtes and Zeilmaker, 1996;Coskun et al, 2000;Huisman et al, 2000;Lundqvist et al, 2002). In a recent study (Rienzi et al, 2002), day 3 embryo transfers with combined evaluation at pronuclear and cleavage stages demonstrated similar results to blastocyst transfers.…”
Section: Discussionmentioning
confidence: 97%
“…In 100 of the women (47%) infertility was caused by female factors, in 62 (29%) it was caused by male factors, and in 50 (24%) no explanation for the infertility was found. The IVF treatment was performed in a standard way, as previously published (7).…”
Section: Methodsmentioning
confidence: 99%
“…In 100 of the women (47%) infertility was caused by female factors, in 62 (29%) it was caused by male factors, and in 50 (24%) no explanation for the infertility was found. The IVF treatment was performed in a standard way, as previously published (7). For HPV tests, smears were taken from the cervix in connection with the infertility work-up or during oocyte retrieval.…”
Section: Methodsmentioning
confidence: 99%